2011
DOI: 10.3399/bjgp11x601398
|View full text |Cite
|
Sign up to set email alerts
|

Does a decision aid help physicians to detect chronic obstructive pulmonary disease?

Abstract: BackgroundNumerous decision aids have been developed recently, but the value they add above that of the initial clinical assessment is not well known. AimTo quantify whether a formal decision aid for chronic obstructive pulmonary disease (COPD) adds diagnostic information, above the physician's clinical assessment. Design and settingSubanalysis of a diagnostic study in Dutch primary care. MethodSixty-five primary care physicians included 357 patients who attended for persistent cough and were not known to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The effect of a CPR when used in conjunction with clinical judgment can only be fully tested in a study design in which participants are assigned (ideally randomly) to apply or receive clinical judgment alone or clinical judgment with access to a CPR. However, studies of diagnostic accuracy or incremental value [ 41 , 42 ] provide a useful and less costly interim step in the evaluation of CPRs prior to a randomised controlled trial and can guide future research.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a CPR when used in conjunction with clinical judgment can only be fully tested in a study design in which participants are assigned (ideally randomly) to apply or receive clinical judgment alone or clinical judgment with access to a CPR. However, studies of diagnostic accuracy or incremental value [ 41 , 42 ] provide a useful and less costly interim step in the evaluation of CPRs prior to a randomised controlled trial and can guide future research.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated negative and positive predictive value, sensitivity, and specificity for these three risk groups (taking one risk group compared with the other two combined), as well as and positive and negative likelihood ratios. The cut-off levels of the three risk groups were based on clinical judgment of the authors and assessment of acceptability of false negative results in other diagnostic studies in primary care 3839 40 41 We carried out a sensitivity analysis around these thresholds using low thresholds of 1% and 2% and high thresholds of 15% and 25%.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity and specificity of clinicians’ predictions or decisions are generally measured under usual practice, and compared to the sensitivity and specificity of the CPR predictions or decisions when applied to the same patients [226, 227]. Some studies have used clinical vignettes [228] while others have used multivariable logistic models to assess the added value of a CPR over and above clinical judgement alone [229]. If it can be demonstrated that the performance of a CPR is superior to unaided clinician judgement, this may aid clinicians’ acceptance and use of the CPR [32].…”
Section: Stages In the Development Of Clinical Prediction Rulesmentioning
confidence: 99%